2015
DOI: 10.1111/nmo.12562
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin receptors as targets for novel motility drugs

Abstract: Constipation arises from a multitude of causes, including aging, spinal cord injury (SCI), and dietary issues. The heterogeneity of inciting factors has made the treatment of constipation particularly challenging. Agonists of ghrelin receptors have beneficial effects on delayed gastric emptying, but less is known about their ability to improve colorectal motility. Recent publications indicate that the activation of the ghrelin receptors in the spinal cord can alleviate constipation due to dietary causes, Parki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…Moreover, this pathway involves multiple neurotransmitters and neuropeptides, including the projection of ghrelin neurons[ 194 - 196 ]. Ghrelin has central and peripheral actions in gut motility, and its receptors are regarded as targets for novel motility drugs[ 197 , 198 ]. Ghrelin fibers originating in the LHA project into the DVC.…”
Section: Cns Mechanism Of Acupuncturementioning
confidence: 99%
“…Moreover, this pathway involves multiple neurotransmitters and neuropeptides, including the projection of ghrelin neurons[ 194 - 196 ]. Ghrelin has central and peripheral actions in gut motility, and its receptors are regarded as targets for novel motility drugs[ 197 , 198 ]. Ghrelin fibers originating in the LHA project into the DVC.…”
Section: Cns Mechanism Of Acupuncturementioning
confidence: 99%
“…Кроме того, не исключен и альтернативный сплайсинг гена грелина с синтезом других грелиноподобных пептидов, например, дез-Gln14-грелина. Более того, возможен синтез и антисмысловых транскриптов, которые могут быть причастны к посттранскрипционной и / или посттрансляционной регуляции гена грелина [9]. В крови грелин представлен такими циркулирующими формами, как неацилированный грелин (UAG), ацилированный грелин (AG) и С-грелин [10].…”
Section: физиология и ключевые эффекты грелинаunclassified
“…Comparable effects were found also upon oral gavage suggesting that an orally active tablet comprising both active ingredients could become the first ever SMC-activating drug treatment against bladder dysfunction and relatedsecondary complications in patients with SCI and WJCCM|www.wjgnet.com [45] . A comparable approach has been explored in recent years to determine the role of electrical stimulation or pharmacological ligands in LDC-mediated potent reflex defecation [46] . Japanese found that ghrelin receptor agonists such as capromorelin or CP464709 administered sc or iv (lumbosacral level) can increase fecal pellet production in SCI rats [47,48] .…”
Section: And Safer Approachmentioning
confidence: 99%